Targeted delivery of paclitaxel by functionalized selenium nanoparticles for anticancer therapy through ROS-mediated signaling pathways. Issue 70 (30th November 2018) - Gong, Guifang; Fu, Bailing; Ying, Caixin; Zhu, Zhiqin; He, Xiaoqian; Li, Yingying; shen, Zhuanxing; Xuan, Qingshan; Huang, Yanqing; Lin, Yan; Li, Yinghua
Abstract : As a therapeutic anticancer agent, the clinical use of paclitaxel (PTX) is limited by its poor water solubility and serious adverse side effects. Abstract : As a therapeutic anticancer agent, the clinical use of paclitaxel (PTX) is limited by its poor water solubility and serious adverse side effects. The targeted-specific intracellular delivery of an anticancer drug as a new therapeutic modality is promising for cancer treatment. The anticancer activity of selenium nanoparticles (SeNPs) with low toxicity and excellent activity has attracted increasing attention for use in biomedical intervention in recent years. In this study, β-cyclodextrin (β-CD)-folate (FA)-modified selenium nanoparticles (SeNPs) loaded with paclitaxel (PTX) (Se@β-CD-FA@PTX) were successfully fabricated through a layer-by-layer method. The nanosystem is able to enter cancer cells through FA receptor-mediated endocytosis to achieve targeted-specific intracellular delivery. Se@β-CD-FA@PTX was found to increase the selectivity between normal and cancer cells. The viability in MCF-7 cells was remarkably lower than in MCF 10A cells, which may promote the specific targeted delivery of Se@β-CD-FA@PTX into MCF-7 cells. Moreover, Se@β-CD-FA@PTX was found to enhance the cytotoxic effect on MCF-7 cells via the induction of apoptosis activation of ROS-mediated p53 and AKT signaling pathways. The results demonstrate that Se@β-CD-FA@PTX nanoparticles provide a strategy for the design of cancer-targeted nanosystems for use in cancer therapy.